Predictors of successful cardioversion of recent-onset atrial fibrillation to sinus rhythm with orally inhaled flecainide. (3rd October 2022) - Ruskin, J; Dufton, C; Maupas, J; Crijns, H; Elvan, A; De Jong, J; Oosterhof, T; Tuininga, Y; Badings, E; Aksoy, I; Nuyens, D; Van Dijk, V; et al.
Abstract: Background: Height, weight, and body mass index (BMI) are well established risk factors for atrial fibrillation (AF) but whether they are also predictors of successful pharmacological cardioversion of AF is unknown. Data from the open-label INSTANT study of flecainide acetate oral inhalation solution (FlecIH) for acute cardioversion of recent-onset symptomatic AF were examined to determine if these anthropometric measures are predictors of successful cardioversion of AF to sinus rhythm (SR) with FlecIH. Methods: Logistic regression was performed on a broad array of patient and disease characteristics to identify predictors of cardioversion success at 90 minutes post-dose, and potential interactions were examined by boundary restriction analysis. Data are presented for patients receiving 120 mg FlecIH. Results: Data from 81 patients (32.1% female) with a mean age of 59.8 years (range: 26.0, 84.0) were included in the analysis. This cohort had a mean weight of 87 kg (range: 57, 150), a mean height of 180 cm (range: 156, 199), and a mean BMI of 26.8 kg/m 2 (range: 17.2, 37.9). A logistic regression model identified height, weight, and BMI as significant predictors of cardioversion success (p<0.01) and a boundary restriction analysis revealed a negative correlation between BMI and conversion rate across the entire dataset (see Figure 1). Clinically significant conversion rates were observed for patients with BMI values that were considered normal (BMI <25 kg/m 2 = 53%; 95% CI: 36, 70), overweight (BMI ≥25 and <30 kg/m 2 = 47%; 95% CI: 29, 64), and obese (BMI ≥30 and <35 kg/m 2 = 43%; 95% CI: 17, 69); however, none of the severely obese patients (BMI ≥35 mg/m 2 ) had their AF successfully converted to sinus rhythm (see Figure 2). Conclusions: Successful cardioversion of recent onset AF with 120 mg FlecIH was observed in normal, overweight, and obese patients with BMI values <35 kg/m 2 ; however, conversion rate decreases with increasing BMI. Further evaluation of FlecIH dosing in severely obese patients is warranted. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): InCarda Therapeutics